THE IMPACT AND EFFECTIVENESS OF PROJECT-BASED LEARNING IN REMOTE ISLAND SCHOOLS IN SUMATERA - Fera Zasrianita; Ahmad Suradi; Mukhamad Hadi Musolin (Program Studi PGSD Universitas Flores, 2026)
The problem in this research is how the impact and effectiveness of project-based learning in schools on remote islands in Sumatera. The purpose of this study is to analyze the impact and effectiveness of its implementation in remote island schools. The subjects in this research were junior high school students and teachers. The data collection techniques employed were interviews, observation, and documentation, while the data analysis techniques utilized included data collection, reduction, presentation, and conclusion. Project-based learning is an effective learning strategy that can increase students' learning motivation, increase learning effectiveness, and develop their competencies. After introducing project-based learning into the curriculum, research results show that students are interested in this type of learning and can efficiently apply the knowledge and skills they have learned by solving real-world problems, develop creative thinking abilities, practice cooperative learning concepts, accept teamwork, and cultivate career and life planning skills. On the other hand, project-based learning demonstrates self-directed, cooperative, and inquiry-based characteristics. Due to the combination of the lack of progressive teaching strategies and the relative weakness of teaching competence, the traditional teaching methods in these schools give rise to some inefficiencies. This leads to unsatisfactory teaching outcomes, where students from these areas appear to be more passive in their approach to learning compared to their counterparts in urban areas.